LAKI-LAKI 40 TAHUN DENGAN GAMBARAN USG ADENOMYOMATOSUS GALDBLADDER - Widyastuti, Retno; Pramana, Triyanta Yuli (Sultan Agung Islamic University of Semarang, 2023)
Background: Adenomyomatosus gallbladder (GA) is a benign change of the gallbladder wall characterized by excessive epithelial proliferation associated with hyperplasia of the muscularis propria. This situation causes thickening of the gallbladder, so that the gallbladder comet tail artifact appears on an abdominal ultrasound examination. Methods: A 40-year-old man with complaints of right upper quadrant abdominal pain that is colic and recurrent. The patient was hospitalized twice within a week with the same complaint. Ultrasound examination of the patient's lawsuit against GA. The differential diagnosis of this case is chronic cholecystitis and cholesterosis, as seen from complaints of right quadrant abdominal pain and comet tail ultrasound images. Results: Cholecystectomy in patients is indicated for therapy and histopathological diagnosis. The results of histopathological examination obtained a picture that pointed to chronic cholecystitis. Conclusion: Diagnosis by histopathology is necessary in patients with ultrasound images of comet tail artifacts in the gallbladder to determine the patient's treatment and prognosis.